Credit Risk Management in the Banking System of Republika Srpska in Crisis Period - Stanišić, Snježana B (Industrija, 2018)
Considering the character, development and the current economic conditions of business operations in Republika Srpska (undeveloped capital market, inadequate legal regulations for the realization and collection of collaterals, the dominant participation of loan business operations in the overall banking), the greatest attention in controlling the banking sector is paid to the control of loan, liquidity and foreign exchange risks. This sector has recently recorded a decline in non-performing loans and a slight growth in profitability, as shown by negative correlation coefficients a few years ago. The aim of this paper is to focus attention on the NPLs and the possibility of their growth, as well as the discovery of new models for controlling them. In this paper, the method of analysis shows indicators of banking sector’s profitability, total loans and non-performing loans from the onset of the crisis to date. Hypothesis set in this paper is that the participation of non-performing loans in the banking sector of Republika Srpska is too great and threatens loan activities and successful business operation. After a bad experience with two banks and serious problems that depositors have been facing, as they have not received their money and it is questionable whether they will ever get it, it is necessary to more thoroughly monitor business operations of each bank as well as the overall banking sector in order to react in time to prevent major problems.